“Janus-Faced” α-Synuclein: Role in Parkinson’s Disease - Ray, Bipul; Mahalakshmi, Arehally M.; Tuladhar, Sunanda; Bhat, Abid; Srinivasan, Asha; Pellegrino, Christophe; Kannan, Anbarasu; Bolla, Srinivasa Rao; Chidambaram, Saravana Babu; Sakharkar, Meena Kishore (Frontiers in Cell and Developmental Biology, 2021)
Parkinson’s disease (PD) is a pathological condition characterized by the aggregation and the resultant presence of intraneuronal inclusions termed Lewy bodies (LBs) and Lewy neurites which are mainly composed of fibrillar α-syn protein. Pathogenic aggregation of α-syn is identified as the major cause of LBs deposition. Several mutations in α-syn showing varied aggregation kinetics in comparison to the wild type (WT) α-syn are reported in PD (A30P, E46K, H 50Q, G51D, A53E, and A53T). Also, the cell-to-cell spread of pathological α-syn plays a significant role in PD development. Interestingly, it has also been suggested that the pathology of PD may begin in the gastrointestinal tract and spread via the vagus nerve (VN) to brain proposing the gut-brain axis of α-syn pathology in PD. Despite multiple efforts, the behaviour and functions of this protein in normal and pathological states (specifically in PD) is far from understood. Furthermore, the etiological factors responsible for triggering aggregation of this protein remain elusive. This review is an attempt to collate and present latest information on α-syn in relation to its structure, biochemistry and biophysics of aggregation in PD. Current advances in therapeutic efforts towards clearing the pathogenic α-syn via autophagy/lysosomal flux are also reviewed and reported.